STUDI USAHATANI PADI SAWAH (Oryza sativa L) DENGAN BERBAGAI CARA PENGOLAHAN TANAH DI KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Rosnita, .; Ardian, . (Lampung University)
Study on land preparations for lowland rice farming aims at understanding level of labor utilization, cost of production, production and earnings as well as efficiency of lowland rice farming.Â The study observed three types of land preparation, i.e. using hoe, hand tractor, and hydro tiller.Â The study was carried out in Rambah sub-district of Rokan Hulu district from July 205 to January 2006. This research applies survey method. Population in this research is lowland rice farmer at planting season 2005 which amount is 250. The respondent is is grouped into 3 classifications, i.e.: 92 farmers using manual land preparation, 83 farmers using hand tractor, and 73 farmers using hydro tiller. The respondents were selected using stratified proportional random sampling with sample amounts to 13. Quantitative data processing is done using net revenue analysis. Then qualitative analysis is done and the result is presented descriptively.Â Result of research indicates that lowland rice farming system with variously land preparation (manual, hand tractor and hydro tiller) competent is achieved seen from value of Return Cost Ratio that is obtained at each type of land preparation done. The best type is by using hydro tiller because it obtains the biggest production, net income, efficiency and family earnings per hectare compared to the others type of land preparation. Seen from production cost, the biggest production cost per hectare is at manual lowland farming system. Among the three type of lowland rice farming system, the biggest production cost released for labor cost, where the biggest usage of labor is at manual land preparation while the smallest usage of labor is at land preparation by using hydro tiller.